Efisiensi dan nilai tambah usaha mikro penggilingan ikan ‘Cha Cha’ di Kota Bengkulu - Lidya Eka Aprianti; Indra Cahyadinata; Irnad Irnad; Reswita Reswita; Heni Sulistyawati Purwaning Rahayu (University of Insan Cendekia Mandiri, 2025)
This study aims to analyze the efficiency and value-added of the ‘Cha-Cha’ fish milling microenterprise in Bengkulu City. The research employs a quantitative approach, assessing business efficiency through the R/C Ratio calculation and value-added analysis using the Hayami method. The findings indicate that the ‘Cha-Cha’ fish milling microenterprise has an R/C Ratio of 1.4, signifying that the business is both efficient and profitable. The value-added analysis reveals variations in the value-added ratio across different fish types, with gabus laut fish exhibiting the highest ratio (55%), followed by parang-parang fish (49%), gleberan fish (45%), and tenggiri fish (29%). The ‘Cha-Cha’ fish milling microenterprise demonstrates a high level of efficiency and the ability to generate significant value-added, particularly for gabus laut fish-based products.